Manajemen Sarana Prasarana dalam Meningkatkan Akreditasi Madrasah Ibtidaiyah Negeri 2 Kota Sawalunto - Elizasri; Putra, Joni; Fadriati (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Accreditation of the study program is necessary to make sure it never expires. Because it will affect the outcomes of the study program's continued existence as decided by the National Accreditation Board for Higher Education (BAN-PT). Accreditation preparation is a difficult process that demands collaboration and support from all stakeholders to get a respectable accreditation result. The issue is that many parties—especially the school—do not sincerely support the accrediting process. As a result, effective communication is necessary for everyone to show their seriousness and unity. To raise the value of accreditation, this essay explores how infrastructure management may enhance accreditation. This study employs a qualitative descriptive analytical methodology. Min 2 Sawalunto City is the research location. Based on the study's findings, it can be concluded that, from planning to implementation to evaluation, the majority of Sawalunto City's Min 2 teachers believe that the facilities and infrastructure management with accreditation achievement in the area is high. As an educator, manager, supervisor, administrator, leader, and motivator, the school principal has demonstrated good facility and infrastructure management. This has allowed him to create a high-achieving educational institution that meets standards for infrastructure.